Gestión del talento humano y su incidencia en la calidad del servicio de la Corporación Nacional de telecomunicaciones (CNT) CIS Quevedo año 2013 - Tigselema Alvarez, Nadia Estefania (2015)
This Research Project was undertaken using the National Telecommunications Corporation (CNT) CIS Quevedo, achievement Where to Get Information Corresponding topic: Human Resource Management and its Impact on the Quality of Service of the National Telecommunications Corporation (CNT) Quevedo CIS Year 2013. As a general Met Objective To evaluate the Human Resource Management and its Impact on the Quality of Service of the National Telecommunication Corporation (NTC) Cis Quevedo Year 2013. The use of Methodology and Research Methods That can help one having clear goals of the proposed objectives. Analysis of the results obtained Through Surveys and Interview Conducted the manager of the Company v help you analyze data representative Way, confirming the Problem Solution WITH Conclusions. The literature clearly expresses raised Pages Internet and consulted books, which serve para verify the existence of the original sources which was used to….